Signe Hebbe. Un’amicizia svedese di Adelaide Ristori - Franco Perrelli (Drammaturgia)
Signe Hebbe (1837-1925) was one of the most prominent Swedish actresses and singers. Since her stays in Paris, in the mid-1960s, having a deep admiration for Adelaide Ristori, she became her friend and pupil. Around this intimate friendship, in 1880, there was a possibility that Ristori could act a historical drama by Ibsen, which unfortunately did not happen. Following the teachings of Ristori, as well as of Lamperti and Ernesto Rossi, Hebbe introduced an acting style considered more realistic for the categories of the time and as a pedagogue, between 1877 and 1925, contributed to form a generation of important Swedish artists, transmitting the fundamental lesson of her Italian teachers to the mid-20th century.